The Impact of Talent Management Dimensions on Employee Performance in Four-Star Hotels - Yosia Yodan; Bobby W Saputra (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study explores the influence of talent management on employee performance in the hospitality sector, focusing on a mid-sized four-star hotel in Bengkulu, Indonesia. The objective was to analyze the collective and individual effects of 11 talent management dimensions, namely company’s vision and mission, workforce planning and analytics, talent acquisition, performance management, learning and development, succession planning, employee experience, change management, organizational development, total rewards, and diversity, equity, inclusion, on employee performance. A quantitative explanatory approach was employed, collecting data from 25 permanent employees using a questionnaire with a 5-point Likert scale. Multiple linear regression was used to test hypotheses, with classical assumption tests ensuring model validity. The findings revealed that the 11 dimensions collectively significantly impact employee performance, explaining 61.3% of performance variance. However, only employee experience and change management showed significant individual effects, likely due to their role in fostering engagement and adaptability, while other dimensions were not significant, possibly due to high turnover and resource constraints in the hotel setting. In conclusion, prioritizing employee experience and change management can enhance service quality, offering practical strategies for hotel management to improve performance.